Direito penal na era global: garantismo positivo ajustado ao garantismo negativo - Gomes, Thiago Quintas (2009)
This dissertation is the analysis of the complex post-industrial, hedonistic, mass and objective relations, called risk society, and what should the attitude of the criminal law be facing the new diffuse and collective interests, from a globalized world. The criminal law must be prepared to deal with this new reality, which means the adoption of a new dogmatic criminal-legal in the protection of meta-individual properties (human rights of 3rd dimension), but conformed to human rights. Human rights must be ensured in all sizes, which means an adjustment between the positive assurance and the negative assurance in the application of globalized criminal law (dense) in achieving the common good